The best ways oy remembering English new words in memory - soliyeva, Zarnigor (Журнал иностранных языков и лингвистики, 2021)
Abstract: This article deals with how to learn and remember English new words in memory which you are learning everyday. You can know how to focus on vocabulary, to learn new words efficiently and fast, to remind them in mind in long time and also time management. You will be aware of many best ways and techniques. Key words: Vocabulary, new words, mnemonika, key words, adaptation.